2022
DOI: 10.3389/fnut.2022.862900
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Extraction of cAMP From Jujube by Ultra-High Pressure Technology and the Anti-allergic Effect for Peanut Allergy Mouse

Abstract: Jujube contains abundant cyclic adenosine monophosphate (cAMP). In contrast, the extraction technology of cAMP from jujube is still to be explored. In this study, the ultra-high pressure extraction (UHPE) conditions for obtaining the maximum cAMP yield from jujube were optimized. Orthogonal array design (OAD) was applied to evaluate the effects of three variables (pressure, pressure-holding time, and liquid-to-solid ratio) by UHPE on cAMP yield. The results showed that the optimal cAMP yield (1223.2 μg/g) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The liquid-to-solid ratio of 40 mL/g was sufficient to reach the high extraction amount. A similar pattern of results was obtained in the extraction of pectin from navel orange peel through HHP by Sang et al [30]. Therefore, we adopted extraction at 415 MPa for 10 min, 72% ethanol concentration, and a liquid-to-solid ratio of 40 mL/g for further study objects.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The liquid-to-solid ratio of 40 mL/g was sufficient to reach the high extraction amount. A similar pattern of results was obtained in the extraction of pectin from navel orange peel through HHP by Sang et al [30]. Therefore, we adopted extraction at 415 MPa for 10 min, 72% ethanol concentration, and a liquid-to-solid ratio of 40 mL/g for further study objects.…”
Section: Discussionsupporting
confidence: 67%
“…HHP with high-pressures and short-time operation can cause deformation and destruction of the plant cell structures, which will significantly affect the diffusion of the bioactive compounds and accelerate the dissolution [18]. Up to now, many researchers have found that increasing the extraction pressure could improve the penetration rate of solvent into the solid tissue and greatly shorten the extraction time [30]. However, excessive pressure could destroy the structure of flavonoids, lowering the extraction amount [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is often combinedly used with the separation membrane, form a complete set of equipment. However, in the extraction process, the pressure holding time should be fully considered, as too long a pressure‐hold time may introduce some other ineffective components [94] and too short pressure time will lead to incomplete extraction and less eluent. In addition, ultra‐high‐pressure equipments were expensive, all kinds of valves and connectors need high sealing level, sealing materials such as gaskets, sealing rings, etc.…”
Section: Methodsmentioning
confidence: 99%
“…At present, the classical extraction methods of CM and natural products mainly include decoction [25, 26], maceration [27–29], reflux [30, 31], percolation [21], steam distillation [32] and sublimation [33, 34]. With the development of modern separation science and equipment, some new technologies such as ultrasonic wave‐assisted extraction (UAE) [35–38], microwave‐assisted extraction (MAE) [39–42], supercritical fluid extraction (SFE) [43–47], enzyme‐assisted extraction (EAE) [48, 23, 49], membrane separation extraction (MSE) [50–57], ultrafine grinding technology (UGT) [58–64], microporous resin adsorption technology (MRAT) [65–70], semi‐bionic extraction (SBE) [71, 72], immune selective extraction (ISE) [73–77], molecular‐distillation technology [78–82], molecularly‐imprinted polymer extraction (MIPE) [83–88], UPE [89–93], liquid chromatographic extraction (LCE) [94–99], solid‐phase extraction (SPE) [100–107], liquid–liquid extraction (LLE) [108–112], etc. have been given birth to.…”
Section: Methodsmentioning
confidence: 99%